2010
DOI: 10.1073/pnas.1014214108
|View full text |Cite
|
Sign up to set email alerts
|

Structure-guided reprogramming of serine recombinase DNA sequence specificity

Abstract: Routine manipulation of cellular genomes is contingent upon the development of proteins and enzymes with programmable DNA sequence specificity. Here we describe the structure-guided reprogramming of the DNA sequence specificity of the invertase Gin from bacteriophage Mu and Tn3 resolvase from Escherichia coli. Structure-guided and comparative sequence analyses were used to predict a network of amino acid residues that mediate resolvase and invertase DNA sequence specificity. Using saturation mutagenesis and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 35 publications
0
75
1
Order By: Relevance
“…In addition, we have recently determined the structure of N15 Cro bound to consensus cognate DNA (B. M. Hall, M. S. Dubrava, S. A. Roberts and M. H. Cordes, unpublished results), which will allow comparison of docking geometries and contacts for Cro proteins of different fold. Finally, incorporation of in vitro or in vivo evolution (see, e.g., Gaj et al 43 ), including randomization of the coding residues and/or other sites in Cro proteins, might yield improved models of direct and/or contextual effects on specificity and could yield insights not accessible to pure comparative methods or to structure-based design.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we have recently determined the structure of N15 Cro bound to consensus cognate DNA (B. M. Hall, M. S. Dubrava, S. A. Roberts and M. H. Cordes, unpublished results), which will allow comparison of docking geometries and contacts for Cro proteins of different fold. Finally, incorporation of in vitro or in vivo evolution (see, e.g., Gaj et al 43 ), including randomization of the coding residues and/or other sites in Cro proteins, might yield improved models of direct and/or contextual effects on specificity and could yield insights not accessible to pure comparative methods or to structure-based design.…”
Section: Discussionmentioning
confidence: 99%
“…Additional biochemically independent RAD modules could likely be identified from the increasing set of known natural recombinases, (37)(38)(39) or perhaps by engineering synthetic integrase excisionase pairs with altered DNA recognition specificity (40)(41)(42). Such work, along with puzzles of integrating dozens of competing biochemical functions, suggest that engineering increased capacity in vivo data storage systems will help define and challenge the limits of synthetic biology.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, although our optimization was conducted with the native gix core sequence (4143), several studies have shown that zinc finger-Gin or TALE-Gin fusions are active, and in some cases more active, on slightly altered core sites (28,30,31,34,4547). Thus, we next sought to target sequences found within the human genome to test if unmodified human genomic sequences were capable of being targeted by recCas9 and to test if varying the guide RNA and core sequences would increase recCas9 activity.…”
Section: Resultsmentioning
confidence: 99%